A new indicator can assess absorption capacity for carbon dioxide and ocean acidification - Zhibo Wang; Xuegang Li; Jinming Song; Guorong Zhong; Shanshan Liu; Zhipeng He; Jun Ma; Huamao Yuan; Liqin Duan (Communications Earth & Environment)
Abstract The ocean has absorbed 25% of anthropogenic carbon dioxide emissions over the past 40 years, effectively slowing atmospheric carbon dioxide growth but causing ocean acidification. As acidification intensifies, the seawater absorption capacity for carbon dioxide will decline. While the Revelle factor has been used to assess carbon dioxide absorption, it becomes inapplicable at pH < 7.5. Here, we propose a new factor, γCO2, to better measure the absorption capacity for carbon dioxide and acidification. γCO2 decreases with increased partial pressure of carbon dioxide and decreased pH, indicating reduced absorption capacity and intensified acidification. In 2020, global surface ocean γCO2 was 15.50 ± 0.21, a 13% decline since 1992. Projections under SSP5-8.5 anticipate an average γCO2 of 4.72 by 2100, with 61.5% of global ocean regions below the critical threshold of γ CO2  = 3.0, potentially harming aragonite-based organisms.